Santri Character Education: Implementation of Dr. Abdul Karim Zaidan's Thought in Madrasah Aliyah Tahfizhul Qur'an Isy Karima - Mahmudi, Irfan; Tolchah, Moch.; Zakariya, Din M. (FIKROTUNA: Jurnal Pendidikan dan Manajemen Islam, 2025)
This study aims to analyze the implementation of santri character education at Madrasah Aliyah Tahfizhul Qur'an Isy Karima Karanganyar, Central Java, from the perspective of Dr. Abdul Karim Zaidan. Using a qualitative ethnographic approach, this research explores the values, norms, and culture that shape the character of santri through observation, interviews, and documentation. Data triangulation was conducted to verify the validity of the information. At the same time, data analysis used a process of reduction, presentation, and conclusion drawing to understand the practice of character education in depth. The results show that the character education model in this madrasah uses a holistic approach that integrates Islamic values with modern education theory. Methods such as modeling, habituation, teaching through Qur'anic stories, giving advice, discipline, and targhib create an effective character-building process. Values such as piety, independence, honesty, discipline, social care, tolerance, and responsibility are internalized through daily routines, teaching and learning activities, and extracurricular activities. This model not only focuses on moral development but also supports academic achievement, such as the success of santri in science olympiads and Al-Qur'an memorization competitions. This research makes a practical contribution to the Islamic character education literature by showing how religious values can be integrated into the formal education system to form a generation with superior personalities. This model can be a reference for other educational institutions designing holistic and value-based education programs.